Comparative study of microstructures and mechanical properties of in situ Ti–TiB composites produced by selective laser melting, powder metallurgy, and casting technologies. Issue 17 (17th June 2014) - Attar, H.; Bönisch, M.; Calin, M.; Zhang, L.C.; Zhuravleva, K.; Funk, A.; Scudino, S.; Yang, C.; Eckert, J.
Abstract